Use of Chemical Probes to Detect Mitochondrial ROS by Flow Cytometry and Spectrofluorometry - Chen, Jing (Methods Enzymol, 2014)
Aerobic respiration is a major source of energy in eukaryotic cells. In this setting, ATP production by the mitochondrial respiratory chain relies on the availability of NADH and FADH(2) to donate protons and electrons. The flux of electrons down the electron transport chain, based on a series of oxidation–reduction reactions, releases energy that allow for the transport of H(+) ions across the inner mitochondrial membrane. The resulting proton-motive force is employed to drive ATP synthesis, while the final acceptor of the electrons flowing through the respiratory chain if molecular oxygen. A side effect of this process is the generation of reactive oxygen species (ROS). While mitochondrial ROS (mtROS) production has been linked to many pathological conditions (i.e., aging and tumorigenesis), recent evidence suggests that multiple cells, including malignant cells, employ these by-products of energy production as signals to control various cellular processes. Here, we describe protocols to use chemical probes for measuring mtROS production in intact cells by flow cytometry and spectrofluorometry.